Complications and Mortality Following One to Two-Level Anterior Cervical Fusion for Cervical Spondylosis in Patients Above 80 Years of Age. Issue 9 (1st May 2017) - Puvanesarajah, Varun; Jain, Amit; Shimer, Adam L.; Singla, Anuj; Shen, Francis; Hassanzadeh, Hamid
Abstract : Study Design: A retrospective database review. Objective: The aim of this study was to determine the complication and mortality rates in patients 80 years of age and older who were treated with anterior cervical fusion surgery and to compare these rates against those of other elderly patients. Summary of Background Data: Cervical spondylosis is frequently observed in the elderly and is the most common cause of myelopathy in older adults. With increasing life expectancies, a greater proportion of patients are being treated with spine surgery at a later age. Limited information is available regarding outcomes following anterior cervical fusion surgery in patients 80 years of age or older. Methods: Medicare data from the PearlDiver Database (2005–2012) were queried for patients who underwent primary one to two-level anterior cervical spine fusion surgeries for cervical spondylosis. After excluding patients with prior spine metastasis, bone cancer, spine trauma, or spine infection, this cohort was divided into two study groups: patients 65 to 79 (51, 808) and ≥80 years old (5515) were selected. A cohort of matched control patients was selected from the 65 to 79-year-old and 90-day complication rates and 90-day and 1-year mortality rates were compared between cohorts. Results: The proportion of patients experiencing at least one major medical complication was relatively increased by 53.4% in patients aged ≥80 years [odds ratio (OR) 1.63]. Patients 80 years of age or older were more likely to experience dysphagia (OR 2.16), reintubation (OR 2.34), and aspiration pneumonitis (OR 3.17). Both 90-day (OR: 4.34) and 1-year (OR 3.68) mortality were significantly higher in the ≥80 year cohort. Conclusion: Patients 80 years of age or older are more likely to experience a major medical complication or mortality following anterior cervical fusion for cervical spondylosis than patients 65 to 79 years old. Dysphagia, aspiration pneumonitis, and reintubation rates are also significantly higher in patients 80 years of age or older. Although complication rates may be higher in this patient population, carefully selected patients could potentially derive much benefit from surgery and should not be screened out solely on the basis of age. Level of Evidence: 4